Using platelet concentrates to treat maxillofacial tissue lesions - Ruijia Liu; Siqi Chen; Peng Wang; Peng Wang; Ruiye Bi; Ruiye Bi (Frontiers in Bioengineering and Biotechnology)
ObjectivesPlatelet concentrates (PCs), which are blood products that are abundant in platelets and growth factors, have become pivotal in treating maxillofacial tissue lesions due to their capacity for promoting bone and soft tissue recovery. This review will provide some recent progress of the use of platelet concentrates to treat lesions on maxillofacial tissues.SubjectsWe reviewed the mechanisms by which PCs promote wound healing and tissue recovery and summarized the application of PCs in the treatment of lesions on maxillofacial tissues, including medication-related osteonecrosis of the jaw, post-extraction wound healing, implant surgery, temporomandibular joint diseases, and periodontal tissue restoration.ResultsPC promotes the attachment and proliferation of osteoblasts, as well as the synthesis and deposition of collagen fibers by stimulating the AFK pathway and releasing growth factors and cytokines, such as secreting GFs, VEGF, TGF-β, etc. They also induce angiogenesis, inhibit bone resorption, promote the healing of soft tissues, relieve symptoms, reduce postoperative complications and maintain implant stability.ConclusionPCs may be used as an adjuvant therapy in the treatment of lesions on maxillofacial tissues. However, more studies should refine the preparation and treatment methods for platelet concentrates and establish a foundation for their extensive application.